Time behavior of the Hα spectral line and the molecular hydrogen spectral line in hydrogen plasma in the Uragan-2M stellarator - Bondarenko, V.M.; Pavlichenko, R.O.; Zamanov, M.V.; Kovtun, Y.V.; Lozin, O.V.; Kozulia, M.M. (Problems of Atomic Science and Technology, 2023)
The studies of the scenario of hydrogen plasma creation with two sequential RF discharges during one pulse were carried out for the Uragan-2M stellarator. The first-stage discharge initiated the hydrogen pre-ionization at the generator anode voltage of 4 kV. The second-stage discharge was performed at the generator anode voltage selected from 6 to 9 kV. As result, plasma with an electron density up to 3.9·10¹⁸ m⁻³ was produced in a confinement volume. An increase of voltage resulted in an earlier appearance of signals of electron density, the intensity of the Hα spectral line, and the intensity of the molecular hydrogen spectral line. The increase of the time-dependent intensities of these signals was also registered.